Heteroligand nanoarchitectonics of functionalized gold nanoparticle for Hg2 detection - Ku Ismail, Ku Syaridatul Irma; Ahmad Tajudin, Asilah; Ikeno, Shinya; Amir Hamzah, Amir Syahir (Springer, 2022)
Mercury is one of the priority metals classified as a human carcinogen, according to the U.S. Environmental Protection Agency and the International Agency for Research on Cancer. This metallic element has a high degree of toxicity, is known to induce multiple organs damage, and has severe adverse effects on human health and the environment, even at low levels of exposure. It has many forms in soil, such as inorganic mercury. In this work, two types of tripeptides: proline-cysteine-histidine (PCH) and γ-L-glutamyl-L-cysteinyl-glycine (glutathione, GSH), were individually immobilized onto gold nanoparticles (AuNPs) surfaces with 20 nm in size via covalent coupling. In a monoligand system, only a particular tripeptide-AuNPs will be used as capturing agents for Hg2+, while in a heteroligand system, two different tripeptide-AuNPs will be used simultaneously in a mixture. Both tripeptides formed stable complexes with soft and hard metal ions. The interaction of heteroligand enhances the sensitivity and selectivity of the plasmonic sensor for Hg2+. This system was incorporated with β-mercaptoethanol (BME), which acts as a spacer between the surface-bound ligand. The heteroligand PCH/GSH-AuNPs was found to be more effective compared to both monoligand systems PCH-AuNPs and GSH-AuNPs with absorbance reading (A730/A524) of 0.808, 0.373 and 0.609, respectively. Upon the addition of metal ions, the red-to-blue color change and the degree of AuNPs aggregation formed by the heteroligand system were doubled when compared to the monoligand system. The finding was supported by absorption spectra, Transmission Electron Microscopy (TEM) analysis, and Dynamic Light Scattering (DLS) spectroscopy. The limit of detection (LOD) for Hg2+ detection was 25 parts per billion (ppb). The heteroligand system was further validated by conjugating tripeptides onto different sizes of AuNPs (20 nm and 100 nm). This new approach can constitute a more effective detecting system targeting small molecules.